2006
DOI: 10.1038/sj.bjp.0706793
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic modulation of Ca2+‐activated K+ channels in proliferating A7r5 vascular smooth muscle cells

Abstract: Modulation of Ca2+‐activated K+ channels (KCa) has been implicated in the control of proliferation in vascular smooth muscle cells (VSMC) and other cell types. In the present study, we investigated the underlying signal transduction mechanisms leading to mitogen‐induced alterations in the expression pattern of intermediate‐conductance KCa in VSMC. Regulation of expression of IKCa/rKCa3.1 and BKCa/rKCa1.1 in A7r5 cells, a cell line derived from rat aortic VSMC, was investigated by patch‐clamp technique, quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
(65 reference statements)
4
50
1
Order By: Relevance
“…Upregulation of K Ca 3.1 channels has been found to promote excessive VSMC proliferation and migration induced by either mitogens (platelet-derived growth factor and EGF) or balloon catheter injury. [13][14][15] However, it is unknown whether AGEs is involved in the K Ca 3.1 channel regulation. In the present study, we demonstrated that AGE-BSA increased K Ca 3.1 current density and enhanced K Ca 3.1 channel protein expression in AGEs and K Ca 3.1 channels Li-Mei Zhao et al cultured rat VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upregulation of K Ca 3.1 channels has been found to promote excessive VSMC proliferation and migration induced by either mitogens (platelet-derived growth factor and EGF) or balloon catheter injury. [13][14][15] However, it is unknown whether AGEs is involved in the K Ca 3.1 channel regulation. In the present study, we demonstrated that AGE-BSA increased K Ca 3.1 current density and enhanced K Ca 3.1 channel protein expression in AGEs and K Ca 3.1 channels Li-Mei Zhao et al cultured rat VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…K Ca 3.1 channels are the predominant Ca 2 þ -activated K þ channels in proliferative smooth muscle cells but not in mature contractile cells. [11][12][13][14] The expression of K Ca 3.1 channels is increased in VSMCs in coronary arteries from patients and in aortas of ApoE À / À mice with atherogenesis, and K Ca 3.1 channel blocker markedly slows down the development of atherosclerosis in ApoE À / À mice. 16 However, reports related to the regulation of K Ca 3.1 channels are limited in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mitogens such as bFGF, PDGF, or VEGF have been found to distinctly up-regulate K Ca 3.1 in several cell types (15,21). Conversely, we and others have recently demonstrated in models of experimental angiogenesis (15), post-interventional arterial restenosis (17,19), atherosclerosis (26), and endometrial cancer (27), that selective pharmacological inhibition or knockdown of K Ca 3.1 suppresses mitogen-driven cell proliferation and ameliorates disease progression.…”
mentioning
confidence: 99%
“…Whereas the first directly mediate Ca 2ϩ inflow, the latter regulate membrane potential and thus provide the driving force for Ca 2ϩ entry (13). In particular, the intermediate-conductance K Ca (K Ca 3.1) has been shown to play an important role in promoting mitogenesis in several tissues such as the endothelium (15,16), vascular smooth muscle (17)(18)(19), and T lymphocytes (20) as well as in several cell lines including A7r5 neonatal aortic smooth muscle cells (21), 10T1/2-MRF4 myogenic fibroblasts (22,23), HMEC-1 dermal endothelial cells (15), and some cancer cell lines (24,25).…”
mentioning
confidence: 99%